Scheduling based on a dynamic resource connection; IOP Conference Series: Materials Science and Engineering; Vol. 177 : Mechanical Engineering, Automation and Control Systems (MEACS 2016) - Nagiyev A. E.; Botygin I. A. Igor Aleksandrovich; Sherstneva A. I. Anna Igorevna; Konyaev P. A. (Information technologies in Mechanical Engineering, 2017)
Title screen